LACTAGOGUE EFFECT OF UYUP-UYUP (TRADITIONAL MEDICINE) AND Sauropus androgynus Merr EXTRACT ON PIGEON INGLUVIES GLANDS - Ika Puspita Sari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
Sauropus androgynus Merr. and uyup-uyup have been used as lactagogue traditional medicine since long time ago, but the pharmacological mechanism was unclear. This research has been done to determine prolactin induction of S. androgynus Merr and uyup-uyup as lactagogue agents. S. androgynus Merr leaf extract and uyup-uyup were given to the pigeon for 7 and 14 consecutive days, the epithelium tunica mucous of ingluvies glands induced by prolactin was then determine. The result showed that S. androgynus Merr. leaf extract and uyup-uyup have lactagogue effect as determined by prolactin induction. The induction of prolactin after S. androgynus Merr leaf extract administration (dose 54 mg/kg Body Weight (BW) for 14 days comparable to that of moloco B12 (dose 189 mg/kg BW) after 7 days administration (p<0.05).Key words : lactagogue, prolactin, tunica mucous